Invertendo a cena: o cinema com vida na formação cultural docente - Melo, José Sebastião Andrade de (2019)
This work sought to reflect on the contributions, possibilities and limits of the use of cinema in the promotion of teacher cultural education in the perspective of the Critical Theory of Society. Would cinema be a facilitator in teacher training processes? What kind of influence could an experience with cinema play in the process of teacher cultural formation? I tried to answer these two questions by investigating how the genesis of the relation between cinema and education in our country was constituted historically, how cultural formation is present in the curricula of the degrees and what the possibilities of the use of cinema for the promotion of this formation. The methodology used methods of bibliographic research such as narrative review, documentary research and autobiographical narrative. The discussion about cultural formation had as theoretical contribution the concepts of formation (Bildung) and semiformation (Halbbildung) present in the essays that compose the works "Theory of Semiformation", "Education and Emancipation" by Theodor W. Adorno and "Dialectics of Enlightenment" of Theodor W. Adorno and Max Horkheimer. In the documentary analysis of the curricula of the undergraduate courses of the public universities in Minas Gerais, the absence of disciplines related to the themes of teacher aesthetic and cultural formation was verified. I attempted, through an autobiographical account, to make a historical rescue of the ten years of the Cinema Com Vida project, describing its actions, the works exhibited, its different phases, how my encounter with the films occurred in the moments that I participated in the project and which were the contributions of this participation to my personal and professional identity. Finally, it was possible to recognize the importance of aesthetic experiences and cinematographic language that may favor not only richer and more stimulating educational practices but also a more complete formation of the individual who teaches.